2005
DOI: 10.1007/s00412-005-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Type II topoisomerase activities in both the G1 and G2/M phases of the dinoflagellate cell cycle

Abstract: Dinoflagellate genomes are large (up to 200 pg) and are encoded in histoneless chromosomes that are quasi-permanently condensed. This unique combination of chromosomal characteristics presents additional topological and cell cycle control problems for a eukaryotic cell, potentially exhibiting novel regulatory requirements of topoisomerase II. The heterotrophic dinoflagellate Crypthecodinium cohnii was used in this study. The topoisomerase II activities throughout its cell cycle were investigated by DNA flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…The degree of eventual decondensation was comparable to those observed in cation-chelated [12] or with topo II inhibitor-treated LCCs [37] ( Figure S3B) in which swelled nuclei filled the size of a normal cell. This suggested that condensins were involved in LCC compaction, likely in the restraint of proposed superhelical modules [7].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The degree of eventual decondensation was comparable to those observed in cation-chelated [12] or with topo II inhibitor-treated LCCs [37] ( Figure S3B) in which swelled nuclei filled the size of a normal cell. This suggested that condensins were involved in LCC compaction, likely in the restraint of proposed superhelical modules [7].…”
Section: Discussionsupporting
confidence: 70%
“…This was consistent with LCC decompaction in some ak-cells, as observed in chelation-mediated LCC decompaction in EDTA-treated nuclei [12]. As an independent control, we conducted a set of experiments with topoisomerase II inhibitor (AMSA) that induced C. cohnii LCC decondensation [37]. As in the case of some ak-cells (T = 33, transects 11-12,13-14, 19-20, and T = 70; Figure S3A), the diffused DAPI-staining (after AMSA treatment) of the whole swelled nucleus filled the whole cells ( Figure S3B), suggesting decondensed LCCs resulting from CcSMC4p knockdown.…”
Section: Prolong Ccsmc4p-knockdown Led To S-phase Impediment With Nucsupporting
confidence: 79%
See 2 more Smart Citations
“…As in the case of histones, acetylation removes positive charges, thereby reducing the affinity between the histones and the DNA (79). As in the case of bacterial HU, HCc proteins may also interact functionally with topoisomerases (80–82), which are also involved in DNA replication and condensation, and is persistently expressed throughout the cell cycle of C.cohnii (83). In the presence of topoisomerase II, local topological changes of DNA filaments can possibly be modulated through the assistance of HCc proteins, in a synergistic and cooperative manner.…”
Section: Discussionmentioning
confidence: 99%